2022
DOI: 10.3389/fcimb.2022.818276
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Early Pathogenic Escherichia coli Infection on the Intestinal Barrier and Immune Function in Newborn Calves

Abstract: We studied the effect of early pathogenic Escherichia coli infection on newborn calves’ intestinal barrier and immune function. A total of 64 newborn Holstein male calves (40–43 kg) were divided into two groups: normal (NG) and test (TG), each with 32 heads. At the beginning of the experiment, the TG calves were orally administered pathogenic E. coli O1 (2.5 × 1011 CFU/mL, 100 mL) to establish a calf diarrhea model. In contrast, the NG calves were given the same amount of normal saline. During the 30 d trial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 58 publications
0
11
0
1
Order By: Relevance
“…There was a significant weight gain in the treated group compared to the non-treated group ( Figure 4 B). When the integrity of the intestinal barrier is damaged, diamine oxidase, D-lactate and bacterial endotoxin are released into the blood [ 26 , 27 ]. We monitored these markers in the blood from tail vein and found them increased in psychologically stressed rat on day 7 ( Figure S2 ), and decreased when treated with JM25-1 on day 11 ( Figure 4 C).…”
Section: Resultsmentioning
confidence: 99%
“…There was a significant weight gain in the treated group compared to the non-treated group ( Figure 4 B). When the integrity of the intestinal barrier is damaged, diamine oxidase, D-lactate and bacterial endotoxin are released into the blood [ 26 , 27 ]. We monitored these markers in the blood from tail vein and found them increased in psychologically stressed rat on day 7 ( Figure S2 ), and decreased when treated with JM25-1 on day 11 ( Figure 4 C).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, C. parvum degrades occludin, claudin 4, and E-cadherin in murine enteroid-derived monolayer and intestines ( Kumar et al., 2018 ). Pathogenic E. coli also disturbs genes associated with epithelial integrity in colons of newborn calves ( He et al., 2022 ). Such overall rearrangements of the host cell cytoskeleton including aggregation and disassembly of actin would be key for the colonization of C. parvum ( Yu et al., 2020 ) and other enteropathogens.…”
Section: Discussionmentioning
confidence: 99%
“…and Shigella spp. was noticed in colonic microbiota from newborn calves challenged by pathogenic E. coli ( He et al., 2022 ) and in fecal microbiota of calves with naturally occurring diarrhea regardless of the pathogen ( Gomez et al., 2017 ; Zeineldin et al., 2018 ; Jang et al., 2019 ; Gomez et al., 2022 ). Interestingly, we observed that microbiota from C. parvum challenged calves supplemented with colostrum could be more resilient compared with microbiota from calves fed only milk replacer.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of diarrhea with pathogenic E. coli seems to be negatively related to the abundance of Lactobacillus. In a study conducted to investigate pathogenic E. coli effects on the intestinal immunity of orally infected dairy calves, the higher E. coli abundance was related to a lower abundance of Lactobacillus [30] . On the other hand, reduced microbial diversity has been observed in calves with watery feces (diarrhea) vs. normal feces in healthy calves [31] .…”
Section: Probiotics Against Diarrhoea and For Host Immunity And Healthmentioning
confidence: 99%